The Perfect Storm: Rapid Progression of Diabetic Ketoacidosis in Pediatric Diabetes in the Setting of COVID-19 - Rachel Modarelli, MD (Elsevier, 2021)
Objective: The coronavirus disease 2019 (COVID-19) pandemic has introduced countless challenges to the medical field. Although pediatric patients have been reported to have lower rates of COVID-19 mortality, the presence of pre-existing conditions can heighten the severity of their clinical presentation. This report discusses the potential influence COVID-19 might have on diabetic ketoacidosis. Methods: Our patient, a 6-year-old girl with known type 1 diabetes, presented with acute onset of abnormal breathing and altered mental status. The day prior, she had 1 episode of emesis, diarrhea, and abdominal pain but no fever. She presented to an outside hospital and was reported to have agonal breathing with a Glasgow Coma Scale score of 8 (eyes open to pain, no verbal response to stimuli, and localized pain). She was promptly intubated, and the initial laboratory tests revealed severe diabetic ketoacidosis (DKA). A family member had COVID-19, and she also tested positive for COVID-19. Results: Our patient’s rapid progression and severity of illness require a discussion of how COVID-19 might affect diabetes and indicate opportunities for improving clinical practice in children with pre-existing diabetes. We discussed how COVID-19 might change the underlying pathophysiology of DKA and cause metabolic complications. Possible mechanisms include binding to angiotensin-converting enzyme 2 receptors and enabling a proinflammatory “cytokine storm.” Additionally, ketoacidosis and altered mental status have been present in patients with COVID-19 without diabetes, which might potentiate the symptoms in developing DKA. Conclusion: Prompt recognition of DKA is warranted, as caregivers may attribute the symptoms to COVID-19 rather than to DKA, resulting in an increased severity of illness on presentation with acute symptom onset, as described in this report.